Direct Demonstration That Loop1 of Scap Binds to Loop7: A CRUCIAL EVENT IN CHOLESTEROL HOMEOSTASIS - Zhang, Yinxin (J Biol Chem, 2016)
Cholesterol homeostasis is mediated by Scap, a polytopic endoplasmic reticulum (ER) protein that transports sterol regulatory element-binding proteins from the ER to Golgi, where they are processed to forms that activate cholesterol synthesis. Scap has eight transmembrane helices and two large luminal loops, designated Loop1 and Loop7. We earlier provided indirect evidence that Loop1 binds to Loop7, allowing Scap to bind COPII proteins for transport in coated vesicles. When ER cholesterol rises, it binds to Loop1. We hypothesized that this causes dissociation from Loop7, abrogating COPII binding. Here we demonstrate direct binding of the two loops when expressed as isolated fragments or as a fusion protein. Expressed alone, Loop1 remained intracellular and membrane-bound. When Loop7 was co-expressed, it bound to Loop1, and the soluble complex was secreted. A Loop1-Loop7 fusion protein was also secreted, and the two loops remained bound when the linker between them was cleaved by a protease. Point mutations that disrupt the Loop1-Loop7 interaction prevented secretion of the Loop1-Loop7 fusion protein. These data provide direct documentation of intramolecular Loop1-Loop7 binding, a central event in cholesterol homeostasis.